2002
DOI: 10.1046/j.1365-2621.2002.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt concentrations and temperature on the quality and shelf‐life of brined anchovies

Abstract: In this study, the shelf‐life and quality of anchovies brined at different concentrations and stored both at refrigerator and ambient temperature conditions were investigated. Sensory, microbiological and chemical analyses of samples were made during storage trials for up to 150 days in order to investigate their quality. The samples stored at ambient temperature showed poor quality at the end of the storage trial. The best quality was observed with the samples that were brined at 22 and 26% salt concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 13 publications
12
45
0
2
Order By: Relevance
“…This may be due to making of ammonical odor by the characteristic strong odor of Chepa. Autolytic enzymes might have caused de-amination of protein resulting in the formation of volatile bases [30,31,32,33]. Although the observed values of the present study are within the acceptable limit as suggested for fishery product by Connell [34].…”
Section: Total Volatile Base Nitrogen (Tvb-n) Content Of Chepa Shutkisupporting
confidence: 39%
“…This may be due to making of ammonical odor by the characteristic strong odor of Chepa. Autolytic enzymes might have caused de-amination of protein resulting in the formation of volatile bases [30,31,32,33]. Although the observed values of the present study are within the acceptable limit as suggested for fishery product by Connell [34].…”
Section: Total Volatile Base Nitrogen (Tvb-n) Content Of Chepa Shutkisupporting
confidence: 39%
“…Thus, consumers are very concerned with halal certificate, also recognation from department of health and Food and Drugs Control Department from government institution. This concern is in line with some empirical studies in some country or region that despite the preserving aim of such local methods, these products are still under risk of several hazards (Köse, 2010) and reported to carry high potential risk for human health for halophilic pathogenic bacteria, histamine and parasites (Tsai et al 2006;Huss et al 2003;Karaçam et al, 2002;Kuda et al 2002;Mah et al 2002;Lehane and Olley, 2000;FDA, 2001;Kirschbaum et al 2000;Essuman, 1992) and a significant body of scientific literature documents that consumers nowadays are more interested in healthy food products to prevent diseases and maintain healthy living (Krutulyte, 2010). Verbeke and Ward (2006) reported that consumers are selective in the attention they pay to different label cues.…”
Section: Quality Dimensionssupporting
confidence: 55%
“…Maturing brined fish products at room temperature present health risk for histamine and/or other BAs such as cadaverine, putrescine and tyramine if brining is carried out at 25% and lower salt concentrations (Karaçam et al, 2002;Köse et al, 2007a;Köse et al, 2008a;Köse et al, 2009a). Therefore, unless heavily salted brine (30% and over) is used, maturing and storage of the brined fish should be carried out at cold storage conditions until it reaches to consumer (prior to eating).…”
Section: Histamine and Other Biogenic Amines (Bas)mentioning
confidence: 99%
“…Traditionally processed fish products (TFPs) are reported to carry high potential risk for human health for halophilic pathogenic bacteria, histamine and parasites (Taylor, 1986;Essuman, 1992;Lehane and Olley, 2000;FDA, 2001;Kirschbaum et al, 2000;Karaçam et al, 2002;Kuda et al, 2002;Mah et al, 2002;Murrell, 2002;Huss et al, 2003;Tsai et al, 2006;Huss et al, 2003;EU, 2004;Hansen, 2008). Due to legal criteria set for potential hazards, domestic and international marketing of these products is becoming difficult and limited.…”
Section: Introductionmentioning
confidence: 99%